2018
DOI: 10.11144/javeriana.upsy16-5.asrr
|View full text |Cite
|
Sign up to set email alerts
|

Apoyo social, resiliencia y región de origen en la salud mental y la satisfacción vital de los inmigrantes

Abstract: Se analiza la relación del apoyo social y la resiliencia con la satisfacción vital y la salud mental de los inmigrantes, y las diferencias en dichas variables según la región de origen (África, Europa, Latinoamérica y Asia). En el estudio han participado 1094 inmigrantes que residen en España. Los resultados de la regresión por pasos muestran que la tenacidad, el apoyo social de la familia y de los autóctonos, y el control personal son los mejores predictores de la satisfacción vital. La tenacidad, el apoyo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 43 publications
(39 reference statements)
1
16
0
11
Order By: Relevance
“…This is explained by the fact that immigrants initially seek contact and support from their compatriots, but as they settle and become integrated in the receiving country, they encounter more contact and support from the native population. This aspect has been shown to be a good indicator of the social integration of immigrants (García-Cid, Hombrados-Mendieta, Gómez-Jacinto, Palma-García, & Millán-Franco, 2017), although we should continue to analyse this issue. It has been shown that cultural proximity has a positive influence on almost all of the variables of social inclusion analysed in this study (Martínez et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…This is explained by the fact that immigrants initially seek contact and support from their compatriots, but as they settle and become integrated in the receiving country, they encounter more contact and support from the native population. This aspect has been shown to be a good indicator of the social integration of immigrants (García-Cid, Hombrados-Mendieta, Gómez-Jacinto, Palma-García, & Millán-Franco, 2017), although we should continue to analyse this issue. It has been shown that cultural proximity has a positive influence on almost all of the variables of social inclusion analysed in this study (Martínez et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…This might be due to the collective's needs being satisfied by the native community to a larger extent than by their fellow citizens. Native population are sources of information about the traditions and habits of the host country (Domínguez-Fuentes and Hombrados-Mendieta, 2012;García-Cid et al, 2017). Therefore, when SOC develops thanks to positive interactions with the native population it plays a vital role in the process of integration and well-being faced by migrants (Searle and Ward, 1990).…”
Section: After Analyzing Direct Effectsmentioning
confidence: 99%
“…When individuals decide to migrate, they usually leave their families behind as well as their closest social ties and support networks that protect their health and well-being (Han and Choe, 1994;Runyan et al, 1998;García-Cid et al, 2017;Millán-Franco et al, 2019a). Migrants settling in a new country must adapt to the traditions and symbols of the new community, which contributes to reduce the sense of community (SOC) from their countries of origin and build a new SOC in the host country (Bathum and Baumann, 2007;Hombrados-Mendieta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that emotional support increases the level of satisfaction among migrants and has a positive impact on their wellbeing (Aroian, 1992). SS from native friends has also been highlighted as the network that best predicts SWL and integration in the host country (García‐Cid, Hombrados‐Mendieta, Gómez‐Jacinto, de las Olas Palma‐García, & Millán‐Franco, 2017). These differences in results have been explained by ethnic differences between study samples (Liang & Bogat, 1994), the frequency and availability of establishing relationships in the host country (García, Ramírez, & Jariego, 2002), working conditions and the legal status of migrant workers (Plaza et al, 2005), or time of residence in the host country (Millán‐Franco, Gómez‐Jacinto, Hombrados‐Mendieta, González‐Castro, et al, 2019).…”
Section: Social Support Satisfaction With Life and Gender In The MImentioning
confidence: 99%
“…Culture shock is much lower among Latin American migrants than among other migrant groups in Spain as they share the values, symbols, and language of the host society. In general, SWL is greater among Latin American migrants than among other migrant groups in Spain (García‐Cid et al, 2017).…”
Section: Present Studymentioning
confidence: 99%